2002
DOI: 10.1093/eurpub/12.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Fear of crime and health in residential tower blocks: A case study in Liverpool, UK

Abstract: The evidence suggests elderly residents believe tower blocks provide safe accommodation. However, feelings of safety in these 'fortresses' do not generally extend to walking in neighbouring streets. Fear of crime erodes quality of life and is associated with poorer health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 11 publications
1
71
1
4
Order By: Relevance
“…Not only does this study provide evidence in the health literature of whether neighborhood environment matters, 20,21 but also advances the literature by demonstrating how the neighborhood social environment affects individual health status. While associations between crime rates and mental health have been found, 44,45 we did not find a direct association with self-rated health. By expanding the institutional performance model, we argue that an individuals' residential environment is relevant in their personal evaluation of their self-rated health.…”
Section: Discussioncontrasting
confidence: 90%
“…Not only does this study provide evidence in the health literature of whether neighborhood environment matters, 20,21 but also advances the literature by demonstrating how the neighborhood social environment affects individual health status. While associations between crime rates and mental health have been found, 44,45 we did not find a direct association with self-rated health. By expanding the institutional performance model, we argue that an individuals' residential environment is relevant in their personal evaluation of their self-rated health.…”
Section: Discussioncontrasting
confidence: 90%
“…Previous research on crime and health has found crime to be positively related to a variety of health outcomes including selfassessed health, 37-39 physical functioning, 39 coronary heart disease, 40 adherence to inhaled glucocorticoids, 41 health-related quality of life, 42 and adverse birth events. 43 Though of growing interest, prior research is inconsistent regarding the association between crime or perceptions of crime and the likelihood of engaging in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low income neighborhoods are generally perceived as less cohesive (Cagney, Browning, & Wen, 2005). Neighborhoods that are less cohesive are often, in turn, less safe (e.g., Greene, Gilbertson, & Grimsley, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Among these respondents, people were more likely to report poorer physical and emotional health if they perceive their neighborhoods as unsafe. However, safety concerns are 11 significantly lower among individuals who report higher perceptions of neighborhood cohesion (Greene, Gilbertson, & Grimsley, 2002). In Wales, individuals' greater perceived neighborhood cohesion is directly related to better mental health and buffers the effect of deprivation on health (Fone, Dunstan, Lloyd, Williams, Watkins, & Palmer, 2007).…”
Section: Neighborhood Cohesion and Healthmentioning
confidence: 95%